Creación de manual de marca y de posicionamiento digital para la empresa Fumiservicios y Asociados Guva SAC - Cordova Pezo, Luanha Ruth (2023)
The Peruvian environmental sanitation company, Fumiservicios y Asociados Guva S.A.C. had a lack of visual identification and had limited digital communication. That is why, considering the characteristics of the company and the primary (companies) and secondary (heads of household) public, the objective of this project is to 1 establish a company visual identity, through the creation of a brand manual; and as objective 2, digitally position the company through a digital communication strategy. The materials and strategies were worked on in two different phases: Phase 1 was developed during the Covid-19 situation (May - July 2021) and the materials developed were implemented digitally. However, phase 2 takes place in the current situation (Oct. - Nov. 2023), in which improvements and updates to the materials of phase 1 were made, and will be implemented in the period from January to March of the year 2024, depending on the cessation of extortion in Lima, since it directly affects the company as it is located in San Martín de Porres, one of the highest risk districts. The brand manual includes, among its main elements, the isotype, typography, corporate colors and human illustration in the likeness of the company's General Manager, Tío Guva, whose objective is to bring the company closer to its target audience. Likewise, the digital communication strategy covers organic and paid content on social networks (LinkedIn, Facebook and Instagram) and website, working on SEO and SEM.